(untitled) (Bangladesh Journal of Psychiatry, 2019)
Kleptomania was a rare impulse control disorder characterized by the recurrent inability to resist the urge to steal items not needed for personal use or monetary gain. Here was a case of a 17-years-old girl presenting with repeated stealing for the last 7 years which was not planned rather impulsive. Both pharmacological and psychological interventions were executed maintaining firm adherence and close monitoring. Considerable improvement of the patients was evident thereafter. The case gave a hopeful message to the mental health professionals to treat these patients more effectively in the future. More researches regarding the management of kleptomania was recommended to be carried out. Bang J Psychiatry 2019; 33(2): 34-35